Governing Nonconformity: Gender Presentation, Public Space, and the City in New Order Indonesia. Issue 4 (November 2021) - Hegarty, Benjamin
Abstract : The regulation of public space is generative of new approaches to gender nonconformity. In 1968 in Jakarta, the capital of Indonesia, a group of people who identified as wadam —a new term made by combining parts of Indonesian words denoting "femininity" and "masculinity"—made a claim to the city's governor that they had the right to appear in public space. This article illustrates the paradoxical achievement of obtaining recognition on terms constituted through public nuisance regulations governing access to and movement through space. The origins and diffuse effects of recognition achieved by those who identified as wadam and, a decade later, waria facilitated the partial recognition of a status that was legal but nonconforming. This possibility emerged out of city-level innovations and historical conceptualizations of the body in Indonesia. Attending to the way that gender nonconformity was folded into existing methods of codifying space at the scale of the city reflects a broader anxiety over who can enter public space and on what basis. Considering a concern for struggles to contend with nonconformity on spatial grounds at the level of the city encourages an alternative perspective on the emergence of gender and sexual morality as a definitive feature of national belonging in Indonesia and elsewhere.